Demand management based design of residential solar power supply system: a techno-economic evaluation (2012)
"With high solar radiation across Nigeria, solar power system can become a viable solution to the Nigeria's electricity power crisis if the problem of high capital cost of solar power supply system can be addressed. In this study the use of demand management based design approach has been explored for reducing the capital cost of residential solar power supply system. Utilities and energy demands of thirty randomly picked homes in selected residential areas were studied. The houses were classified into one, two and three rooms' residential apartments. New energy efficient appliances that can deliver the same or higher utility values as those already in use in these houses were classified into one, two and three rooms' residential apartments. New energy efficient appliances that can deliver the same or higher utility values as those already in use in these houses were identified and proposed as replacement to cut energy demand. Cost analysis of replacement with these energy star appliances was carried out. Solar system designs and associated cost models were developed for both the existing demand system and the proposed energy efficient demand system. For comparative analysis, appliances replacement cost was factored into the associated solar system capital cost. The average total energy demands were 1255W, 1785W, and 2185 for one, two, and three bedroom flats respectively while equivalent demands for energy efficient system are 389W, 820W, and 851W respectively. The cost of designing and installing a solar power with the replaced appliances exhibits a significant reduction of 64.88%, 64.5% and 62.16% for the one, two and three rooms residential set up respectively. We conclude that an integrated demand management design approach is very useful in reducing the capital cost of residential solar systems. "